Shaligram Pilgrimage in the Nepal Himalayas - Walters, Holly (Book collections on Project MUSE., 2020)
For roughly two thousand years, the veneration of sacred fossil ammonites, called Shaligrams, has been an important part of Hindu and Buddhist ritual practice throughout South Asia and among the global Diaspora. Originating from a single remote region of Himalayan Nepal, called Mustang, Shaligrams are all at once fossils, divine beings, and intimate kin with families and worshippers. Through their lives, movements, and materiality, Shaligrams then reveal fascinating new dimensions of religious practice, pilgrimage, and politics. But as social, environmental, and national conflicts in the politically-contentious region of Mustang continue to escalate, the geologic, mythic, and religious movements of Shaligrams have come to act as parallels to the mobility of people through both space and time. Shaligram mobility therefore traverses through multiple social worlds, multiple religions, and multiple nations revealing Shaligram practitioners as a distinct, alternative, community struggling for a place in a world on the edge.